Noise-like pulse generation in 1.95 µm region using bulk α-alumina saturable absorber - Mohd Yusoff, Norita; Mohamed Ahmed, Mahmoud Hazzaa; Ng, Eng Khoon; Alresheedi, Mohammed Thamer; Mayzan, Mohd Zul Hilmi; Mahdi, Mohd Adzir (Elsevier, 2023)
This work presents a tapered fiber decorated with bulk α-alumina with 4.08% modulation depth and 21.67 MW/cm2 saturation intensity which was responsible to induce noise-like pulse (NLP) in an “eye-safe” wavelength region. The light-matter interaction within evanescent field of ultrathin tapered fiber established NLP in a ring configuration of thulium-doped fiber laser with a broad spectral bandwidth of 45 nm centered at 1948 nm wavelength. The NLP was emitted at 11.36 MHz repetition rate in a net anomalous laser cavity. The generated pulse had a maximum pulse energy of 2.46 nJ at 1587 mW pumping power. The robustness of the NLP performance was validated with 3 h stability test, which opens new possibilities for future research of this material in the wavelength of exceeding 1.9 μm.